Long-term exposure to fine particulate matter and dementia incidence: A cohort study in Hong Kong. (15th February 2021) - Ran, Jinjun; Schooling, C. Mary; Han, Lefei; Sun, Shengzhi; Zhao, Shi; Zhang, Xiaohong; Chan, King-Pan; Guo, Fang; Lee, Ruby Siu-yin; Qiu, Yulan; Tian, Linwei
Abstract: Recent studies suggested that long-term exposure to fine particulate matter (PM2.5 ) was related to a higher risk of dementia incidence or hospitalizations in western populations, but the evidence is limited in Asian cities. Here we explored the link between long-term PM2.5 exposure and dementia incidence in the Hong Kong population and whether it varied by population sub-group. We utilized a Hong Kong Chinese cohort of 66, 820 people aged ≥65 years who were voluntarily enrolled during 1998–2001 and were followed up to 2011. Prevalent dementia cases were excluded based on the face-to-face interview at baseline. We ascertained the first occurrence of hospitalization for all-cause dementia and major subtypes during the follow-up period. We assessed PM2.5 concentrations using a satellite data-based model with a 1 × 1 km 2 resolution on the residential address. Cox proportional hazards models were adopted to estimate associations of annual mean PM2.5 exposure with dementia incidence, adjusting for potential confounders. We identified 1183 incident cases of all-cause dementia during the follow-up period, of which 655 (55.4%) were cases of Alzheimer's disease, and 334 (28.2%) were those of vascular dementia. We found a positive association between annual mean PM2.5 exposure and all-cause dementia incidence in the fully adjusted model. The estimated hazard ratio was 1.06 (95% confidence interval (CI): 1.00, 1.13) per every 3.8 μg/m 3 increase in annual mean PM2.5 exposure. And the estimated HRs for Alzheimer's disease and vascular dementia were 1.03 (95% CI: 0.94, 1.12) and 1.09 (95% CI: 0.98, 1.22), respectively. We did not find effect modifications by age, sex, BMI, hypertension, diabetes, or heart disease on the associations. Results suggest that long-term exposure to PM2.5 is associated with a higher risk of dementia incidence in the Asian population. Graphical abstract: Image 1 Highlights: Evidence of long-term PM2.5 effects on dementia in Asian cities is limited. PM2.5 exposure was positively associated with dementia in Hong Kong aged population. The association of vascular dementia was stronger than that of Alzheimer's disease. Effect modifications by age, sex, BMI, co-existing diseases were not evident. Abstract : Long-term exposure to PM2.5 was positively associated with the increased risk of all-cause dementia incidence in the Hong Kong aged population. Potential positive associations with the incidence of Alzheimer's disease and vascular dementia were also observed but not of statistical significance. The association of vascular dementia seemed to be stronger than that of Alzheimer's disease. Effect modifications by age, sex, BMI, and co-existing diseases were not evident in the associations.